2023
DOI: 10.1038/s41467-023-43377-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NAD-RNA species and ADPR-RNA decapping in Archaea

José Vicente Gomes-Filho,
Ruth Breuer,
Hector Gabriel Morales-Filloy
et al.

Abstract: NAD is a coenzyme central to metabolism that also serves as a 5′-terminal cap for bacterial and eukaryotic transcripts. Thermal degradation of NAD can generate nicotinamide and ADP-ribose (ADPR). Here, we use LC-MS/MS and NAD captureSeq to detect and identify NAD-RNAs in the thermophilic model archaeon Sulfolobus acidocaldarius and in the halophilic mesophile Haloferax volcanii. None of the four Nudix proteins of S. acidocaldarius catalyze NAD-RNA decapping in vitro, but one of the proteins (Saci_NudT5) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Recent studies have demonstrated the presence of NAD-RNAs in archaeal model organisms, with the highest NAD cap concentration reported so far 9 , 16 , thereby extending the existence of NAD-RNAs to all three domains of life. Given the widespread occurrence of NAD-RNAs and the conservation of TIR domains across various phyla 59 , 60 , we hypothesize that the deNAMing capacity of TIR domain might be evolutionarily conserved.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Recent studies have demonstrated the presence of NAD-RNAs in archaeal model organisms, with the highest NAD cap concentration reported so far 9 , 16 , thereby extending the existence of NAD-RNAs to all three domains of life. Given the widespread occurrence of NAD-RNAs and the conservation of TIR domains across various phyla 59 , 60 , we hypothesize that the deNAMing capacity of TIR domain might be evolutionarily conserved.…”
Section: Resultsmentioning
confidence: 92%
“…4c ), suggesting that these enzymes might work together to specifically decap NAD-RNAs. A recent report showed that ADPR-RNA exists in archaea and can be generated from NAD-RNA through the spontaneous loss of NAM 16 . Our findings suggest that TIR-catalyzed NAM removal is another mechanism to generate RNAs capped by ADPR or its variants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore strain-promoted (copper-free) azide-alkyne cycloaddition (SPAAC) (9) and Nanopore sequencing have been applied to identify NAD-RNAs (10). Overall, based on the NAD captureSeq technology, NAD-RNAs have been identified in various bacteria (11,12), including Escherichia coli (5,10), archaea (13,14) and eukaryotes (9,1521), highlighting the universal existence of this cofactor-capped RNA species (8).…”
Section: Introductionmentioning
confidence: 99%